The Doctrine of Addai and the letters of Jesus and Abgar - Labubnā bar Sennāḳ (Early Christian apocrypha, 2023)
"The Doctrine of Addai tells the story of how Christianity came to the Syrian city of Edessa. It incorporates and adapts a correspondence between Jesus and the Syrian king Abgar, who wrote to Jesus requesting healing from a long-term illness. In his response, Jesus promises to send him an apostle, Addai (sometimes called Thaddaeus), who will heal Abgar's disease and establish Christianity in his kingdom. The exchange between Jesus and Abgar and Edessa's subsequent evangelization by Addai functions as a founding myth for Christianity in the region, which likely did become Christian under a later King Abgar in the early third century. But the activities and interactions of Addai in Edessa reflect a later time: the fifth century, when Christians in the East were embroiled in a conflict over reforms enacted by the Bishop Rabbula. These complexities of Syrian Christian history are all made clear in the introduction and rich commentary that accompanies this updated English translation of the Doctrine of Addai and related texts--including early witnesses to the Abgar/Jesus Correspondence in papyri and inscriptions, and selections from the Ecclesiastical History of Eusebius of Caesarea, the Acts of Thaddaeus, and the Acts of Mar Mari." --